Interlinking tourism destination competitiveness determinants, travel and tourism competitiveness index and tourism performance / Mohd Hafiz Mohd Hanafiah - Mohd Hanafiah, Mohd Hafiz (Institute of Graduate Studies, UiTM, 2017)
This thesis contributes to the tourism destination competitiveness (TDC) literature by providing validated measures of TDC determinants and empirical understanding of the impact of TDC determinants on the Travel and Tourism Competitiveness Index (TTCI) ranking and tourism performance. The purpose of this thesis was to articulate and test the relationships between TDC determinants, TTCI ranking, and tourism performance by taking into account the effects of the macroeconomic condition of destinations. This study provides an analytic review of TDC determinants with a twofold objective, that is, to test the TDC determinants’ statistical soundness and to assess the ability of the determinants in explaining the TTCI ranking and tourism performance complexity. Also, the relationship between TTCI ranking and tourism performance will be examined, and the moderating effect of destination’s macroeconomic conditions was tested and analysed. The structural relationship was explored through the examination of underlying TDC theoretical model, as reflected in the literature review. Data from 115 destinations were used to test the hypothesized relationships via partial least square-structural equation modeling (PLS-SEM). Measurement instruments of TDC determinants, TTCI ranking, tourism performance and macroeconomic conditions were adopted and validated based on data collected from secondary sources…